Segmentation of the Common Carotid Artery Intima Media Using Active Contour Models - Hesko, Branislav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
Ultrasound measurements of the human carotid artery intima media thickness are conventionally obtained using manual tracing between tissue layers. This article consists of different approach, when intima media thickness is determined automatically. Tissue layers are detected by use of active contour segmentation. This method does not use any type of gradient, only intensity based image is needed. Therefore, robustness to speckle noise is present. A total of 15 carotid artery ultrasound images is analyzed to determine wall thickness. For evaluation, each of the images contains manually added marks by an expert.
Keywords: Ultrasound imaging; Active contour methods; Segmentation; Carotid artery; Intima media thickness